Plan de emprendimiento de una agencia de servicios de marketing digital dirigidos a las pymes de la ciudad de Machala. - Bermeo Reyes, Diego Vicente (2017)
This research work is done in order to see the high impact of digital marketing for pymes in the city of Machala, and in turn to know the behavior of the client, and thus to be able to demonstrate that this well executed service is Positively effective for the development of companies and thus make a clear advantage over their competencies. Through the studies carried out within this work can be determined that social media digital marketing, direct marketing and new trends such as blended marketing, based on the scheme of the 4c same that always help in the market positioning issue and effectively advertise Through online marketing, developed through an exhaustive research, reflects the most important parts of the digital marketing service for pymes, a proposal that is oriented directly to small and medium enterprises in assistance of useful and optimal services in regard To digital communication, between company and client, in which it has a location in the city of Machala and with the objective of creation itself that is to provide assistance services in relation to digital marketing for small and medium enterprises, making it a Effective and efficient tool for promotion, and disseminated N of the different products in the virtual platform, highlighting the ease of decision making in the purchase of goods or services, before the different companies that will be our customers in the future, achieving with this innovative idea a greater participation in the market, and To highlight in a potential increase in supply and demand for the present service, the province of gold and the city of Machala itself is gradually entering a boom in global digital development, which has captured the attention of all especially the Trading companies of different products, this is a worldwide phenomenon. As we are living in the digital age under this great factor and being aware of the lack of attention to the present need creates the proposal called digital marketing service for pymes in the city of Machala. This idea is based on the example of similar projects developed in first world countries united states, Spain, Italy and Japan itself, a quality of these countries that have among themselves, have integral technology. And combining technology with sales is an excellent formula, whose objective is to serve through digital marketing to the different pymes of our city, both in promotion, diffusion, interaction and development of campaigns of introduction and brand positioning. We are characterized by our persevering spirit and fervently believe in our project. Developing results is our mission, being the main allies for the growth of your business is our vision. These effective solutions are very practical and accessible in their application, always taking care of the aesthetics, the economic value to pay and the profitability to receive from our service to our client, and from his client to our client.